Economic evaluation of ceftazidime-avibactam vs. polymyxin B for treatment of hospital-acquired and ventilator-associated bacterial pneumonia - Jessica Matuoka; Daniela Vianna Pachito; Filipe Piastrelli; Lorena Cristina Correa Fehlberg; Haliton Alves de Oliveira Junior (Brazilian Journal of Infectious Diseases)
Ventilator-associated pneumonia is one of the most common infections in Intensive Care Units (ICU). It is frequently caused by multidrug-resistant pathogens (including carbapenems) and is an important health issue. It may result in severe clinical consequences, with higher healthcare utilization and high economic burden. Timely and appropriate treatment is key to obtaining better outcomes and allocational efficiency. Currently, the treatment options for carbapenem-resistant pathogen infections are limited, usually based on polymyxin, aminoglycosides, or combination therapy, as well as novel antibiotic therapies including Ceftazidime/Avibactam (CAZ-AVI). CAZ-AVI has shown activity against gram-negative pathogens and is currently used for the treatment of Ventilator-Associated Pneumonia (VAP). To better inform healthcare professionals and help promote a rational use of antibiotic therapy, a cost-effectiveness analysis was conducted to compare the cost-effectiveness of CAZ-AVI versus polymyxin B in ICU patients with VAP from the Brazilian National Supplementary Health Agency perspective over a 5-year time horizon. CAZ-AVI had higher total costs and resulted in more Quality-Adjusted Life Years (QALY) gained when compared with polymyxin B. At a willingness-to-pay threshold of BRL 40,000.00/QALY gained, CAZ-AVI was the cost-effective strategy (ICER: BRL 35,298.65/QALY gained). Nephrotoxicity in patients treated with polymyxin B, hospitalization utility, and treatment duration were the variables that most influenced the results. In the probabilistic sensitivity analysis, CAZ-AVI was cost-effective in 55 %–89 % of the interactions. The evidence suggests that CAZ-AVI results in lower mortality and nephrotoxicity rates, which might have contributed to more QALYs gained and a favorable ICER, despite the higher costs. This study was registered on the Open Science Framework database (Protocol https://doi.org/10.17605/OSF.IO/SP2EJ).